2014
DOI: 10.2151/sola.2014-026
|View full text |Cite
|
Sign up to set email alerts
|

Detection of “Invisible Waterspout” Using 3D Scanning Doppler Lidar

Abstract: A three-dimensional coherent Doppler lidar (3D-CDL) and an interval camera were used to detect a cyclonic "invisible waterspout" very close to the sea surface near Ikeshima island, Nagasaki Prefecture, on 21 December 2010. High-resolution 3D-CDL images revealed that the waterspout had a subscale vortex. The deduced core diameter of the waterspout (subscale vortex) was 234 m (105 m), and the vorticity was 0.17 s −1 (0.32 s −1). The estimated maximum wind speed of the waterspout was about 17 m s, which falls int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 13 publications
0
1
0
Order By: Relevance
“…Doppler lidar was also used to detect an otherwise-invisible small-scale vortex over the sea i.e. a waterspout (Fujiwara and Fujiyoshi 2014). Ito and Niino (2014) applied a Particle Image Velocimetry (PIV) method to estimate the wind field in a dust devil which they encountered in Arizona, USA.…”
Section: Japanmentioning
confidence: 99%
“…Doppler lidar was also used to detect an otherwise-invisible small-scale vortex over the sea i.e. a waterspout (Fujiwara and Fujiyoshi 2014). Ito and Niino (2014) applied a Particle Image Velocimetry (PIV) method to estimate the wind field in a dust devil which they encountered in Arizona, USA.…”
Section: Japanmentioning
confidence: 99%
“…This process caused stretching and contraction of the vortices and produced multiple NSTs. Fujiwara and Fujiyoshi [10] attempted to detect invisible waterspouts using Doppler lidar volume scans. They showed that vortices along shear lines produced by gust fronts were generated in the early stages of waterspouts.…”
Section: Introductionmentioning
confidence: 99%